2016
DOI: 10.1016/j.tiv.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

A combined in vitro approach to improve the prediction of mitochondrial toxicants

Abstract: Drug induced mitochondrial dysfunction has been implicated in organ toxicity and the withdrawal of drugs or black box warnings limiting their use. The development of highly specific and sensitive in vitro assays in early drug development would assist in detecting compounds which affect mitochondrial function. Here we report the combination of two in vitro assays for the detection of drug induced mitochondrial toxicity. The first assay measures cytotoxicity after 24h incubation of test compound in either glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 54 publications
3
63
0
Order By: Relevance
“…Specifically, the bioenergetic profile of KCN-AAS-35 suggests that the compound is an ETC inhibitor, since KCN-AAS-35 decreased the oxygen consumption rate, decreased the reserve capacity, and increased the extracellular acidification rate in a dose dependent manner. 36 These results confirmed that KCN-AAS-35 is capable of inhibiting cellular respiration in eukaryotes. While there are notable differences between Gram-positive and mitochondrial ETCs, many inhibitors, such as antimycin A, rotenone, and sodium cyanide, are capable of inhibiting both types of ETCs.…”
Section: Resultssupporting
confidence: 64%
“…Specifically, the bioenergetic profile of KCN-AAS-35 suggests that the compound is an ETC inhibitor, since KCN-AAS-35 decreased the oxygen consumption rate, decreased the reserve capacity, and increased the extracellular acidification rate in a dose dependent manner. 36 These results confirmed that KCN-AAS-35 is capable of inhibiting cellular respiration in eukaryotes. While there are notable differences between Gram-positive and mitochondrial ETCs, many inhibitors, such as antimycin A, rotenone, and sodium cyanide, are capable of inhibiting both types of ETCs.…”
Section: Resultssupporting
confidence: 64%
“…Among other tested cell lines of different tissue and species origin, the T-lymphoblastoid origin CEM cell line was the most susceptible to NHC treatment, with CC 50 values 3-to 4-fold lower than in other cell lines tested (see Table S1); therefore, the CEM cell line was chosen to evaluate the potential for NHC to cause mitochondrial toxicity. In addition, the HepG2 cell line was also chosen since HepG2 cells have been traditionally used to evaluate mitochondrial toxicity (2,14,20,21) and have demonstrated their utility. NHC is efficiently converted in cells to its 5=-triphosphate.…”
Section: Resultsmentioning
confidence: 99%
“…The D* EIDD-2061 in this experiment is 13.2. In second analogous experiment repeat, the D* EIDD-2061 was measured to be 11.5. mitochondrial quantity or the decrease of mitochondrial function due to decrease in mitochondrial protein quantity or protein function (13,21,23), the effect of long-term incubation with NHC on both mitochondrial number and lactate production in treated cells was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In a context of screening for drug safety, the combination of cytotoxicity testing using a conventional 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay (60) made more specific of mitochondrial dysfunction by substituting galactose to glucose as hydrocarbon energy source (61) and of measurements of changes of mitochondrial spare capacity has been shown to be an accurate and sensitive approach for assessing the potential of in vivo mitochondrial toxicity of various molecules (62). Using an improved global metabolic assay (MTS), we showed that mitochondrial dysfunction and inhibition of CYTox I expression develop before cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%